THE KINETICS OF REACTIONS BETWEEN PYRITE AND O2-BEARING WATER REVEALED FROM IN SITU MONITORING OF DO, EH AND PH IN A CLOSED SYSTEM - Kameia G.; Ohmotob H. (My University, 2000)
Details of reactions between pyrite and water initially equilibrated with the atmosphere (pO2 = 0.2 atm and pCO2 = 10-3.5 atm) were investigated in a closed-system, batch reactor at 25°C and 37°C. The values of dissolved O2 content (DO), Eh, and pH of the experimental solutions were continuously monitored during the reactions that lasted from ~30 h to ~160 h; the SO42- content was also determined for solutions periodically withdrawn from the experimental system. The changes with time in these variables of the experimental solutions suggest that pyrite decomposition proceeds through three major overall reactions. The first is the dissolution of iron monosulfide, commonly present on fractured pyrite surfaces, to generate Fe2+, SO42-, and H2: ''FeS''+4H2O#Fe2++SO42-+4H2 Dissolved CO2 facilitates this reaction, but dissolved O2 is not involved. The second reaction is the oxidation of pyrite by dissolved O2 to generate Fe2+ and SO42-: FeS2+7/2O2+H2O#Fe2++2SO42-+2H+ The third is the reaction to produce ferric hydroxide and SO42-: FeS2+15/4O2+7/2H2O#Fe(OH)3(s)+2SO42-+4H+ Reactions (1) and (2) appear to be first-order with respect to [O2] as suggested by Manaka (1998). The rate law for pyrite decomposition at pH = 5.7 +/- 0.3 and T = 25°C is determined to be: -d[py]/dt = 10-5.3+/-0.5 [O2] (mol/m2/s) for reaction (1) and -d[py]/dt = 10-6.0+/-0.5 [O2] (mol/m2/s) for reaction (2). The pH dependency of the reaction rates was not determined in this study.In each stage of pyrite (and/or iron monosulfide) decomposition, the overall reactions can be divided into two principal reactions: (i) dissolution of minerals by acid (e.g., FeS to Fe2+ and H2S; FeS2 to Fe2+ and HS2-), and (ii) oxidation of aqueous sulfides, polysulfides, and Fe2+ by H2O and O2. The rates of the dissolution reactions are generally faster than those of the redox reactions; the latter reactions only become significant when the reaction products from the former reactions have increased significantly.Previously, the rates of pyrite oxidation by dissolved O2 were generally estimated from the rates of increases in Fe2+ and/or SO42- of solutions in the experimental systems that are open to O2. However, those rates may be much higher or lower than the true rates: the true rates may be accurately determined from the rates of decreases in dissolved O2 during reactions with pyrite in a closed system. Examination of the equilibrium relationships among the DO, Eh, pH, SO42- and Fe2+ of experimental solutions suggest that equilibrium is generally established among H+, OH-, e-, H2, Fe2+, and Fe(OH)3, but not between these species and O2, SO42-, or pyrite, and that the Eh-pH-H2 values of most groundwaters are generally buffered by ferric hydroxide (+/- clays +/- carbonates).